2006
DOI: 10.1002/jcp.20969
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Prn‐p gene and stable transfection of Prn‐p cDNA in leukemia MEL and neuroblastoma N2a cells increased production of PrPC but not prevented DNA fragmentation initiated by serum deprivation

Abstract: Prion protein (PrP(C)) via its isoform PrP(SC) is involved in the pathogenesis of transmissible spongiform encephalopathies (TSEs). We observed that murine erythroleukemia (MEL) cells arrested in phase G(1) undergo transcriptional activation of Prn-p gene. Here, we explored the potential role of activation of Prn-p gene and cytosolic accumulation of PrP(C) in growth arrest, differentiation, and apoptotic DNA fragmentation by stably transfecting MEL and N2a cells with Prn-p cDNA. Stably transfected MEL cells (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Thus, some reports have suggested that PrP c might have a protective function against Baxinduced cell death, oxidative stress, and hypoxic injury (1). Conversely, in several experimental systems, overexpressed or endogenous PrP c both lead to exacerbated cellular responsiveness to apoptotic insults (2)(3)(4)(5)(6)(7). In addition, cell degeneration in the nervous system of old transgenic mice harboring high copy number of the PrP c gene had been observed (8).…”
mentioning
confidence: 99%
“…Thus, some reports have suggested that PrP c might have a protective function against Baxinduced cell death, oxidative stress, and hypoxic injury (1). Conversely, in several experimental systems, overexpressed or endogenous PrP c both lead to exacerbated cellular responsiveness to apoptotic insults (2)(3)(4)(5)(6)(7). In addition, cell degeneration in the nervous system of old transgenic mice harboring high copy number of the PrP c gene had been observed (8).…”
mentioning
confidence: 99%
“…In many cell cultures, the enhanced expression of PrP C was proposed to facilitate cytoprotective effects[32]. However, overexpression of exogenously delivered PrP C in MEL cells did not protect the cells against apoptosis initiated by serum withdrawal[33]. We also found that silencing of PrP C did not seem to sensitize cells to apoptosis during differentiation, as demonstrated by a Trypan Blue exclusion assay and by monitoring of Bax expression by qRT-PCR.…”
Section: Discussionmentioning
confidence: 62%
“…For example, the major prion protein (node P23097, highlighted with the red rectangle in Figure 2A) did not existed in K562 but existed in other two cell lines. Experimental studies showed that the over-expression of P23097 failed to protect DNA fragmentation in leukemia cancer cell line but it converted TNF-sensitive cells into TNF-resistant cells in MCF7 breast cancer cell line [4546]. Moreover, the expression of major prion protein were associated with increased lung colonization [47].…”
Section: Resultsmentioning
confidence: 99%